Diseño e implementación de un manual de seguridad e higiene industrial en el trabajo para la mueblería “Josesito” para el período 2012 – 2014 - Muñoz Razo, Mayra Daniela (2015)
The need to improve the safety and industrial hygiene in Josesito Furniture Store has motivated the need to design and implement a manual safety and industrial hygiene, in order to advance in an increasingly competitive market, and improve the Quality of Working Life Talent within the production plant Josesito Furniture Store. Josesito Furniture Store commitment together with employs will be to generate and establish responsibility and commitment to recouse the regulations of all that relates to the field of Industrial Hygiene allowing introduce significant improvements for all. Safety and Industrial Hygiene allow a better development of staff within the workshop, with the expectation of an adaptation of the tasks and activities according to the physical capabilities of operators, with the elimination or minimization of physical, chemical, ergonomic and biological, and establishing an awareness of safety and health at work.